Spatial training preserves associative memory capacity with augmentation of dendrite ramification and spine generation in Tg2576 mice - Jiang, Xia (Sci Rep, 2015)
Alzheimer's disease (AD) is the most common neurodegenerative disorder and there is currently no efficient cure for this devastating disease. Cognitive stimulation can delay memory loss during aging and in patients with mild cognitive impairment. In 3 × Tg-AD mice, training decreased the neuropathologies with transient amelioration of memory decline. However, the neurobiological mechanisms underlying the learning-improved memory capacity are poorly understood. Here, we found in Tg2576 mice spatial training in Morris water maze (MWM) remarkably improved the subsequent associative memory acquisition detected by contextual fear conditioning. We also found that spatial training enhanced long term potentiation, dendrite ramification and spine generation in hippocampal dentate gyrus (DG) and CA1 neurons at 24 h after the training. In the molecular level, the MWM training remarkably activated calcium/calmodulin-dependent protein kinase II (CaMKII) with elevation of glutamate AMPA receptor GluA1 subunit (GluA1), postsynaptic density protein 93 (PSD93) and postsynaptic density protein 95 (PSD95) in the hippocampus. Finally, the training also significantly ameliorated AD-like tau and amyloid pathologies. We conclude that spatial training in MWM preserves associative memory capacity in Tg2576 mice, and the mechanisms involve augmentation of dendrite ramification and spine generation in hippocampus.